2016
DOI: 10.1016/j.astropartphys.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter searches using gravitational wave bar detectors: Quark nuggets and newtorites

Abstract: Many experiments have searched for supersymmetric WIMP dark matter, with null results. This may suggest to look for more exotic possibilities, for example compact ultra-dense quark nuggets, widely discussed in literature with several different names. Nuclearites are an example of candidate compact objects with atomic size cross section. After a short discussion on nuclearites, the result of a nuclearite search with the gravitational wave bar detectors Nautilus and Explorer is reported. The geometrical acceptan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…All quark nuggets interact 13 – 15 through gravitational and strong nuclear forces. A brief summary of quark-nugget formation, stability, and compliance with dark-matter requirements 7 35 has been updated from Ref. 17 and is provided for completeness as Supplementary Information : Quark-nugget research summary.…”
Section: Introductionmentioning
confidence: 99%
“…All quark nuggets interact 13 – 15 through gravitational and strong nuclear forces. A brief summary of quark-nugget formation, stability, and compliance with dark-matter requirements 7 35 has been updated from Ref. 17 and is provided for completeness as Supplementary Information : Quark-nugget research summary.…”
Section: Introductionmentioning
confidence: 99%
“…Porter et al [32] and Piotrowski et al [33] reported the absence of sufficiently fast meteor-like objects in the lower atmosphere constrains the flux of quark nuggets (nuclearites) to approximately that required to explain dark matter. Bassan et al [34] looked for quark nuggets (nuclearites) with gravitational wave detectors and found signals much less than expected for the flux of dark matter.…”
Section: Discussionmentioning
confidence: 99%
“…We consider the search for tracklike impulse signatures of these DM candidates. Previous searches for such heavy DM have taken place at large detectors directly [12][13][14][15][16] or through observation of energy loss signatures within neutrino detectors [17] and resonant-bar gravitational wave detectors [18] as well as by looking for characteristic defects left within ancient target materials such as mica or meteorites [19,20]. Fifth-force searches [21][22][23] and existing bounds on DM self-interaction [24] also provide stringent constraints on this parameter space.…”
Section: Introductionmentioning
confidence: 99%